Sickle as Crescent: Islam and Communism in the Netherlands East Indies, 1915-1927 - Hongxuan, Lin (Studia Islamika, 2018)
This paper examines the confluence of Islam and Communism in the Netherlands East Indies from 1915-1927, by studying how Islam and Communism were theorized as compatible. It analyzes the nature of conciliatory discourses linking Communism and Islam by exploring the profuse anti-colonial print culture of the period. This paper examines four corpora of sources: the published writings of Tan Malaka; selected excerpts from two newspapers edited by Haji Misbach and his associates; Tjokroaminoto’s 1924 book, Islam and Socialism; and finally, Soekarno’s 1926 article, published as Nationalism, Islam and Marxism. This paper will conclude with a brief examination of Dutch reports and oral testimony regarding how Islam and Communism figured in the motivations of participants in the 1926-1927 Communist uprisings.DOI: 10.15408/sdi.v25i2.5675